Modelling human pathology of traumatic brain injury in animal models. (23rd April 2019) - Risling, M.; Smith, D.; Stein, T. D.; Thelin, E. P.; Zanier, E. R.; Ankarcrona, M.; Nilsson, P.
Abstract: Traumatic brain injury (TBI) is caused by a head impact with a force exceeding regular exposure from normal body movement which the brain normally can accommodate. People affected include, but are not restricted to, sport athletes in American football, ice hockey, boxing as well as military personnel. Both single and repetitive exposures may affect the brain acutely and can lead to chronic neurodegenerative changes including chronic traumatic encephalopathy associated with the development of dementia. The changes in the brain following TBI include neuroinflammation, white matter lesions, and axonal damage as well as hyperphosphorylation and aggregation of tau protein. Even though the human brain gross anatomy is different from rodents implicating different energy transfer upon impact, especially rotational forces, animal models of TBI are important tools to investigate the changes that occur upon TBI at molecular and cellular levels. Importantly, such models may help to increase the knowledge of how the pathologies develop, including the spreading of tau pathologies, and how to diagnose the severity of the TBI in the clinic. In addition, animal models are helpful in the development of novel biomarkers and can also be used to test potential disease‐modifying compounds in a preclinical setting. Abstract : Content List ‐ Read more articles from the symposium: "Head Trauma in Sports and Risk for Dementia".